PELATIHAN PERAKITAN KOMPUTER PADA MA IBNU SINA KUTONTEGALTIRTO BERBAH SLEMAN YOGYAKARTA - Budi Suyanto; Ahmad Taufiq Akbar; M. Rafid Zufar (Jurnal Padamu Negeri, 2024)
Computers come from the word computer (to compute) which means to calculate. However, in accordance with the development of the times, computers have experienced many improvements, computers do not only function to calculate, but have been used to do various jobs and human activities, such as research, banking, and even education. With the help of computers and other supporting devices such as operating systems and applications, all types of work can be carried out quickly, precisely, and accurately. In completing these tasks, the computer does it automatically based on the instructions given to it. Computer assembly focuses on the introduction and assembly of hardware, to the installation of the operating system. Computer assembly training at MA IBNU SINA Kuton Berbah Sleman Yogyakarta is a community service activity carried out to help students learn more about computer maintenance and use.